Governance, expertise, and the 'culture of care': The changing constitutions of laboratory animal research in Britain, 1876–2000. (June 2022) - Kirk, Robert G.W.; Myelnikov, Dmitriy
Abstract: This article examines why early twenty-first century animal research governance in Britain foregrounds the 'culture of care' as its key problem. It adopts a historical perspective to understand why the regulation of animal research became primarily a problem of 'culture', a term firmly associated with the social relations of animal research, at this time and not before. Drawing on the theoretical insights of Sheila Jasanoff, Stephen Hilgartner and others, we contrast the British regulatory framework under the Cruelty to Animals Act (1876), which established statutory regulation of animal research for the first time in the world, with its successor the Animals (Scientific Procedures) Act 1986 (ASPA), in an attempt to chart two closely related yet distinct 'constitutions' of animal research each shaped by a historically situated sociotechnical imaginary. Across this longue durée, many concerns remained consistent yet inevitably, as the biomedical sciences transformed in scale and scope, new concerns emerged. Animal care, at least as far as it entailed a commitment to the prevention of animal suffering, was a prominent feature of animal research governance across the period. However, a concern for the culture and social relations of animal research emerged only in the latter half of the twentieth century. We account for this change primarily through a gradual distribution of responsibility for animal research from a single coherent community with broadly shared expertise ('scientists' with experience of animal research) to a diversified community of multiple experience and skillsets which included, importantly, a more equitable inclusion of animal welfare as a form of expertise with direct relevance to animal research. We conclude that animal research governance could only become conceived as a problem of 'culture' and thus social relations when responsibility for care and animal welfare was distributed across a differentiated community, in which diverse forms of expertise were required for the practice of humane animal research.